2019
DOI: 10.1038/s41467-019-09364-x
|View full text |Cite
|
Sign up to set email alerts
|

Asgard archaea capable of anaerobic hydrocarbon cycling

Abstract: Large reservoirs of natural gas in the oceanic subsurface sustain complex communities of anaerobic microbes, including archaeal lineages with potential to mediate oxidation of hydrocarbons such as methane and butane. Here we describe a previously unknown archaeal phylum, Helarchaeota, belonging to the Asgard superphylum and with the potential for hydrocarbon oxidation. We reconstruct Helarchaeota genomes from metagenomic data derived from hydrothermal deep-sea sediments in the hydrocarbon-rich Guaymas Basin. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
228
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 193 publications
(238 citation statements)
references
References 71 publications
9
228
1
Order By: Relevance
“…The 2021 MAGs were 133 assignable to 63 different bacterial and archaeal phyla based on genome-aggregate amino acid 134 identity (gAAI) values ( Fig. 3), with over 40 of them affiliated with Candidate Phyla Radiation 135 (CPR) as well as the newly described Asgard superphylum 18,19 . Recent studies have shown that 136…”
Section: Main 47 48mentioning
confidence: 99%
See 1 more Smart Citation
“…The 2021 MAGs were 133 assignable to 63 different bacterial and archaeal phyla based on genome-aggregate amino acid 134 identity (gAAI) values ( Fig. 3), with over 40 of them affiliated with Candidate Phyla Radiation 135 (CPR) as well as the newly described Asgard superphylum 18,19 . Recent studies have shown that 136…”
Section: Main 47 48mentioning
confidence: 99%
“…This is likely attributable to the lack 162 of dissolved oxygen and the presence of gaseous hydrocarbons at the latter sites when compared 163 to the DWH-impacted sites, most of which were aerobic. Archaea are typically associated with 164 the presence of methane and other short-chain and gaseous hydrocarbons as is the case in natural 165 oil seeps where dissolved oxygen is often not detectable18 . In contrast, the deep sea DWH plume 166 at the seafloor was aerobic, presumably leading to enrichment of taxa that differed from those in 167 the sub-surface samples.…”
mentioning
confidence: 99%
“…3b). Five of the six Lokiarchaeon populations also exhibited a 174 13 C-labeling pattern that was suggestive of mixotrophic activity, as they had similar labeling in 175 both the bicarbonate and dEPS incubations (Fig. 3b).…”
mentioning
confidence: 92%
“…All OTUs affiliated with "Candidatus Lokiarchaeota" (n=6) were significantly enriched with 172 13 C in the bicarbonate incubations (CI > 90%), with 5-35% total carbon atoms per Lokiarchaeon 173 population being 13 C -labeled ( Fig. 3b).…”
mentioning
confidence: 99%
See 1 more Smart Citation